Detection of BoHV-1 - Comparative Evaluation of Real Time PCR, Real Time LAMP and Subtyping: - Aslim, Hatice Pelin; Oya Bulut, (Acta Scientiae Veterinariae, 2024)
Background: Bovine Herpesvirus 1 (BoHV-1) is an important bovine pathogen found throughout the world. It causes a subclinical, mild, or severe disease. It has different types of clinical manifestations in respiratory, genital, ocular, and encephalomyelitis forms. The aim of this study was to perform comparative diagnosis of BoHV-1 by Real Time PCR and Real Time LAMP and molecular characterization of BoHV-1. Materials, Methods & Results: In this study, BoHV-1 was investigated in nasal swab samples from cattle with clinical signs of respiratory problems using Real-Time PCR (Polymerase Chain Reaction) methods and the Real-Time Loop-Mediated Isothermal Amplification (LAMP) method, which is a cheap, fast, and reliable technique. BoHV-1 positive samples in both tests were cultured in the Madin-Darby Bovine Kidney (MDBK) cell culture. Conventional PCR was performed for the molecular characterization of the isolated samples. Eight (5.33%) nasal swab samples used in the study were found to be positive by the Real-Time PCR test, while 13 (8.66%) samples were found to be positive by the LAMP test. The results of the McNemar test showed that the difference between Real-Time PCR and Real-Time LAMP tests was not significant (P ˃ 0.05). BoHV-1 was isolated from 3 of 8 samples cultured in cell culture. In the sequence analysis of these three samples after PCR, molecular characterization of the isolates was performed, and they were found to belong to the BoHV-1.1 subtype. These findings indicated that the LAMP method can be used in the rapid diagnosis of BoHV-1 infection, and the BoHV-1.1 subtype should be considered in the fight against infection. Discussion: Many studies have shown that PCR tests are more sensitive than virus isolation (VI). Similarly, in this study, only 3 of the 8 samples found to be positive by Real-Time PCR could be isolated in cell culture. The results of both tests differed in that PCR can detect any viral RNA (infectious whole virus, unpackaged viral genome, even genome strand or subgenomic fragments) whereas VI detects properly packaged and live virus particles. Although no statistical difference was recorded between Real-Time PCR and Real-Time LAMP in this study, a higher rate of positive samples was detected with LAMP, which matched the findings of other reports. These results showed that LAMP is a more resistant to PCR inhibitors and more sensitive test and due to the use of 6 different primers. BoHV-1 continues to cause significant economic losses in the cattle industry around the world. Therefore, a practical, fast, and cost-effective diagnostic tool needs to be used to identify the infection in the affected areas and control it at the earliest. In this context, the LAMP test is a promising method at the field level for the diagnosis and control of BoHV-1 infection and other diseases, as mentioned in other studies. Phylogenetic analysis was performed on 3 swab samples isolated in cell culture, after they were tested by conventional PCR with primers specific to the BoHV-1 gC region, in parallel with other reports. The isolate sequence was aligned using MUSCLE, with the sequences of other isolates obtained by a comparative analysis and multiple sequence alignment was performed in the AliView software. This analysis included the nucleotide sequences of 54 different isolates. All ambiguous locations were removed for each sequence. There were 312 nucleotides in the final dataset. Evolutionary analysis was performed using the Tamura 3-parameter model with the Neighbor-Joining algorithm in MEGA 11; in total, 1,000 iterations (bootstrap) were performed. Similar to the findings of other studies conducted in Turkey, it was determined in this study that the more common BoHV-1 strain in circulation was the BoHV-1.1 strain. Keywords: BoHV-1, molecular characterization, Real-Time LAMP, Real-Time PCR.